Spatial Distribution and Prognostic Implications of Tumor-Infiltrating FoxP3- CD4+ T Cells in Biliary Tract Cancer - Kim, Hyung-Don; Kim, Jwa Hoon; Ryu, Yeon-Mi; Kim, Danbee; Lee, Sunmin; Shin, Jaehoon; Hong, Seung-Mo; Kim, Ki-Hun; Jung, Dong‐Hwan; Song, Gi‐Won; Hwang, Dae Wook; Lee, Jae Hoon; et al. (Cancer research and treatment, 2021)
PurposeThe clinical implications of tumor-infiltrating T cell subsets and their spatial distribution in biliary tract cancer (BTC) patients treated with gemcitabine plus cisplatin were investigated.Materials and MethodsA total of 52 BTC patients treated with palliative gemcitabine plus cisplatin were included. Multiplexed immunohistochemistry was performed on tumor tissues, and immune infiltrates were separately analyzed for the stroma, tumor margin, and tumor core.ResultsThe density of CD8+ T cells, FoxP3- CD4+ helper T cells, and FoxP3+ CD4+ regulatory T cells was significantly higher in the tumor margin than in the stroma and tumor core. The density of LAG3- or TIM3-expressing CD8+ T cell and FoxP3- CD4+ helper T cell infiltrates was also higher in the tumor margin. In extrahepatic cholangiocarcinoma, there was a higher density of T cell subsets in the tumor core and regulatory T cells in all regions. A high density of FoxP3- CD4+ helper T cells in the tumor margin showed a trend toward better progression-free survival (PFS) (p=0.092) and significantly better overall survival (OS) (p=0.012). In multivariate analyses, a high density of FoxP3- CD4+ helper T cells in the tumor margin was independently associated with favorable PFS and OS. ConclusionThe tumor margin is the major site for the active infiltration of T cell subsets with higher levels of LAG3 and TIM3 expression in BTC. The density of tumor margin-infiltrating FoxP3- CD4+ helper T cells may be associated with clinical outcomes in BTC patients treated with gemcitabine plus cisplatin.